Roles, relationships, and motor aggressions: Keys to unveiling the emotions of a traditional sporting game - Pere Lavega-Burgués; Verónica Alcaraz-Muñoz; Carlos Mallén-Lacambra; Miguel Pic (Frontiers in Psychology, 2023)
International organizations such as the UN and UNESCO set priority goals for education in the 21st century. This article shows the educational contribution of the Traditional Sporting Game (TSG) of Bear Guardian and Hunters that involves the three-chained roles. The three roles test players who share a unique social interaction ritual. This study was part of a training experience for university students in physical activity and sports sciences in the theory and practice of motor games subject at INEFC, University of Lleida (Spain). This research investigated the emotional intensity in these three roles, the emotional meaning units, and their correspondence with the emotional triad. This study is a mixed-methods research. After playing the game involved, 131 university students (46 women and 85 men) aged 18–35 years (M = 20.19, SD = 2.42) answered the validated GES-II scale indicating the intensity and causes of five basic emotions. The data were analyzed using different strategies (qualitative data: content analysis; quantitative data: descriptive statistical analysis, inferential and association rules). The methodology employed has revealed part of this game’s secret (intimate and subjective) code: the affectivity invisible to external observation. Among the findings, we highlight: (a) each role originates different intensities and units of emotional meaning; (b) the three roles feedback, need and complement each other in this socio-affective network of interdependent relationships; (c) the Bear is the central role of the game. The emotional meanings concerning the motor aggression of the Bear operate as a magnet that attracts four itineraries of association rules of meanings and emotional triads. In the hands of intelligent, prepared and sustainable teachers, this game can help students learn to live together and educate them to control and respectfully channel motor aggression. In this way, students will be active actors in the process of civilization in favor of sustainable development.